Suicide Disclosure in Suicide Attempt Survivors: Does Family Reaction Moderate or Mediate Disclosure's Effect on Depression?. Issue 1 (29th June 2015) - Frey, Laura M.; Hans, Jason D.; Cerel, Julie
Abstract : Existing literature has found a link between disclosure of a stigmatized identity and improved mental health; however, research on the impact of suicide disclosure to family members is scarce. Suicide attempt survivors ( n  =   74) in the United States were examined to assess whether family reaction moderates or mediates the relationship between suicide disclosure and subsequent depression symptoms. Family reaction did not moderate but did mediate the relationship between disclosure and depression symptoms while controlling for time since most recent attempt. Higher rates of disclosure predicted more positive family reactions, which in turn predicted less severe depression symptoms. Findings indicate that family members can play an essential role in the recovery process after an attempt occurs, which has important implications for both researchers and clinicians who seek to decrease stigma for attempt survivors while simultaneously decreasing the likelihood of future attempts.